Jurisdiction, caseload, and timeliness of State Supreme Courts - (:unkn) unknown (My University, 2016)
This report is on the timeliness of state supreme courts. According to the Appellate Court Performance Standards, expedition is one of the three primary goals state appellate courts should strive to achieve. The other values are fairness and consistency. What is the actual time taken to resolve cases? How do state supreme courts stand in relation to the numerical time frames proposed by the American Bar Association (ABA)? What are the problems of and prospects for comparing state supreme courts with one another? These are the organizing questions addressed in this report.